Methodological Issues in the Design and Analyses of Neonatal Research Studies: Experience of the NICHD Neonatal Research Network - Das, Abhik (Semin Perinatol, 2016)
OBJECTIVE: Impressive advances in neonatology have occurred over the 30 years of life of The Eunice Kennedy Shriver National Institute of Child Health and Human Development Neonatal Research Network (NRN). However, substantial room for improvement remains in investigating and further developing the evidence base for improving outcomes among the extremely premature. We discuss some of the specific methodological challenges in the statistical design and analysis of randomized trials and observational studies in this population. FINDINGS: Challenges faced by the NRN include designing trials for unusual or rare outcomes, accounting for and explaining center variations, identifying other subgroup differences, and balancing safety and efficacy concerns between short-term hospital outcomes and longer term neurodevelopmental outcomes. CONCLUSIONS: The constellation of unique patient characteristics in neonates calls for broad understanding and careful consideration of the issues identified in this paper for conducting rigorous studies in this population.